2008
DOI: 10.1098/rstb.2008.0131
|View full text |Cite
|
Sign up to set email alerts
|

Beyond existence and aiming outside the laboratory: estimating frequency-dependent and pay-off-biased social learning strategies

Abstract: The existence of social learning has been confirmed in diverse taxa, from apes to guppies. In order to advance our understanding of the consequences of social transmission and evolution of behaviour, however, we require statistical tools that can distinguish among diverse social learning strategies. In this paper, we advance two main ideas. First, social learning is diverse, in the sense that individuals can take advantage of different kinds of information and combine them in different ways. Examining learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
272
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(286 citation statements)
references
References 39 publications
11
272
2
1
Order By: Relevance
“…The results of such investigations are corroborated by evidence from controlled laboratory studies, which indicate that people attend to the frequencies of their peers' behaviour, as well as to the payoffs associated with it [23][24][25][26][27][28][29] . In addition, there are indications that the extent to which people resort to social information depends on factors like task difficulty, confidence in their own information 30 and environmental variability 31 .…”
supporting
confidence: 64%
“…The results of such investigations are corroborated by evidence from controlled laboratory studies, which indicate that people attend to the frequencies of their peers' behaviour, as well as to the payoffs associated with it [23][24][25][26][27][28][29] . In addition, there are indications that the extent to which people resort to social information depends on factors like task difficulty, confidence in their own information 30 and environmental variability 31 .…”
supporting
confidence: 64%
“…2, (McElreath et al 2008). Recent experimental work with children has underscored these adult findings, by showing how children use subtle cues of competence, reliability, performance, prestige and intent (Jaswal & Neely 2006;Birch et al 2008;VanderBorght & Jaswal 2009) to figure out whom they will attend to and learn from.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Subsequent experiments have shown that people employ both of these social learning strategies, as predicted, but that payoff bias is typically preferred to conformity. McElreath et al (2008) found this using a simple two-option task of planting wheat or potatoes where one gave higher yields, Morgan et al (2011) using various tasks including mental rotation and perceptual judgements, and Mesoudi (2011b) using a more complex artifactdesign task. In each of these, participants could employ trial-and-error asocial learning, or use some form of social learning.…”
Section: Social Learning Is Payoff-biased and Conformistmentioning
confidence: 99%